A new nearctic species of Atrichopogon (Melohelea) and a redescription of Atrichopogon (M.) chilensis Ingram & Macfie (Diptera: Ceratopogonidae) - Tóthová, Andrea (2009)
A new species of Ceratopogonidae from Canada, Atrichopogon (Meloehelea) ladislavi Tóthová, is described. The Patagonian species Atrichopogon (M.) chilensis Ingram & Macfie is restored from synonymy, its female is redescribed and the male is described for the first time.